Stratigraphy of the Baghanwala Formation, Khewra Gorge, Khewra, Jehlum District; Punjab; Pakistan - Khan, Muhammad Attaullah; Khan, Muhammad Javed (Journal of Himalayan Earth Sciences, 1979)
The Baghanwala Formation consists of variegated shales with thin bedded flaggy sandstone. Stratigraphic studies coupled with the lithology and sedimentary structures revealed that the formation was deposited in a shallow basin under arid and strongly oxidizing environments. Bulk of the sandstone beds are calcareous, with abundant argillaceous material at some stratigraphic levels. Iron oxide pigmentation is dominant. The Baghanwala Formation on the basis of its conformable contact with the underlying Jutana Dolomite is assigned a Late Early Cambrian-Early Middle Cambrian age.